Utilizing spent mushroom substrate for rearing black soldier fly (Hermetia illucens) larvae: enhancing fertilizer efficiency and improving animal feed quality for sustainable agriculture - Kanokkan Kanjanarat; Parichart Laksanawimol; Jittawadee Lersawhanwaree; Sarayut Khan; Anchana Thancharoen (PeerJ)
Spent mushroom substrate (SMS), a byproduct of mushroom cultivation, has high potential as a substrate for rearing animals, including black soldier fly larvae (BSFL). However, due to its low nutrient content, mixing it with other organic waste is necessary to enhance its efficiency and effectiveness. We evaluated three types of SMS—Agrocybe cylindracea, Lentinus polychrous, and Pleurotus pulmonarius—supplemented with mixed vegetables at three different levels (0% (VEG or control), 15%, and 30% (w/w)) and subjected to two pre-treatment processes (non-fermented and fermented). The SMS from three different mushroom types did not differ much in their influences upon BSFL growth performance at a 15% (w/w) SMS supplement, and were similar to VEG. Increasing the SMS level to 30% resulted in smaller larval, prepupal, and pupal weights. Self-fermentation of SMS for two months neither significantly altered its nutrient composition nor affected larval growth. However, it resulted in a better nutrient quality of the BSFL biomass and its frass, which was associated with the nutrient composition in SMS. Accordingly, BSFL decomposition significantly enhanced the efficiency of low-nutrient substrates, resulting in a 6- to 10-fold increased protein content in the larval biomass and higher total nitrogen, phosphorous, and potassium (NPK) levels in their frass compared to raw SMS. Nevertheless, further optimizing the substrate formulation would likely enhance the benefits from available waste materials and so support sustainable agriculture.